Potent neutralization of SARS‐CoV‐2 including variants of concern by vaccines presenting the receptor‐binding domain multivalently from nanoscaffolds. Issue 3 (9th September 2021) - Halfmann, Peter J.; Castro, Ana; Loeffler, Kathryn; Frey, Steven J.; Chiba, Shiho; Kawaoka, Yoshihiro; Kane, Ravi S.
Abstract: The persistence of the global severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic has brought to the forefront the need for safe and effective vaccination strategies. In particular, the emergence of several variants with greater infectivity and resistance to current vaccines has motivated the development of a vaccine that elicits a broadly neutralizing immune response against all variants. In this study, we used a nanoparticle‐based vaccine platform for the multivalent display of the receptor‐binding domain (RBD) of the SARS‐CoV‐2 spike (S) protein, the primary target of neutralizing antibodies. Multiple copies of RBD were conjugated to the SpyCatcher‐mi3 protein nanoparticle to produce a highly immunogenic nanoparticle‐based vaccine. RBD‐SpyCatcher‐mi3 vaccines elicited broadly cross‐reactive antibodies that recognized the spike proteins of not just an early isolate of SARS‐CoV‐2, but also three SARS‐CoV‐2 variants of concern as well as SARS‐CoV‐1. Moreover, immunization elicited high neutralizing antibody titers against an early isolate of SARS‐CoV‐2 as well as four variants of concern, including the delta variant. These results reveal the potential of RBD‐SpyCatcher‐mi3 as a broadly protective vaccination strategy.